Productive performance of Holstein and the crossbreding Kiwi Cross x Holstein cattle - Mogollón García, Henry David (2020)
Introduction. During decades, milk production in the Nariño state has depended on the Holstein breed. For this reason, it is necessary to evaluate a model of milk production that allows to decrease production costs and in turn improves the compositional quality of the milk. Objective. This study aimed to compare milk production and compositional quality of Holstein (HO) and the crossbreed between Kiwi Cross (KC) x HO. Materials and methods: Monthly milk production in HO cows (n=30) and the ones from the F1 of the KC x HO cross (n=40), was measured by adjusting the day in milk (DIM) and milk production by third of lactation, fat, protein and total solids. For the period between October 2016 and May 2017, 9,809 dairy production records were analyzed. Results: Maximum production was 25.8 ± 0.53 vs. 23.2 ± 0.53 l day-1 for HO vs. KC cows (p<0.05), respectively. The DIM was not different; however, in days 60, 90, 150, 180, 210 and 240 the HO group produced more milk than the KC group, with a persistence in the lactation peak until day 60, and from that point onwards milk production showed decreasing rates in both groups. Furthermore, the production per third of lactation was higher (p<0.05) in the first third compared to the second and third periods for HO (13.6±0.56 vs. 11.3±0.5723 and 9.9±0.47 l day-1, respectively) and KC (12.8±0.4505 vs. 10.6±0.66 and 9.5 ± 1.69 l day-1, respectively). Fat content was higher (p<0.05) in KC compared to HO in week one, three and five (4±0.07, 4±0.07, 4±0.07 vs. 3.6±0.12, 3.6±0.11, 3.7±0.09 %, respectively); likewise, protein in week one and four was higher in the KC group compared to HO (3.3±0.04 vs. 3.1±0.05 %; p<0.05). Total solids were 13.3±0.17 vs. 12.5±0.23% (p<0.05) for KC and HO cows, respectively in weeks two and five. Conclusion: Milk production in KC and HO was similar; however, KC improved performance in compositional milk quality, increasing the percentages of fat, protein and consequently, total solids.